2009
DOI: 10.2478/v10045-009-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bio-Rational Insecticides on Selected Biological Aspects of the Egyptian Cotton Leafworm Spodoptera Littoralis (Boisd.) (Lepidoptera: Noctuidae)

Abstract: Effectiveness of 8 bio-rational insecticides, Dipel 2x, BioFly , Agrin, BioGaurd, Spinosad, Neemix, Mectin and Match were tested at recommended dose, half of recommended dose and quarter of recommended dose against 1st, 3rd and 5th instar larvae and the egg masses (24, 48 and 72 h old) of the Egyptian cotton leafworm Spodoptera littoralis (Boisd.) under laboratory conditions.All the bio-rational insecticides provided higher mortality in the first instar larvae comparing to the third and fifth instar larvae, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…It may be due to the former insecticides' ability to remove egg cortex. These findings are in conformity with those reported by Osman and Mahmoud (2009), who reported that Mectin and Spinosad had significant effects on the percentage of egg hatching of the Egyptian cotton leafworm, Spodoptera littoralis (Boisd. ).…”
Section: Discussionsupporting
confidence: 93%
“…It may be due to the former insecticides' ability to remove egg cortex. These findings are in conformity with those reported by Osman and Mahmoud (2009), who reported that Mectin and Spinosad had significant effects on the percentage of egg hatching of the Egyptian cotton leafworm, Spodoptera littoralis (Boisd. ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with. Osman and Mahmoud (2009) mentioned that Dipel 2x, BioFly, Agrin, BioGaurd, Spinosad, Neemix, Mectin and Match provided higher mortality in the first instar larvae of Spodoptera littoralis compared to the third and fifth instar larvae, although Match, Mectin and Spinosad showed also excellent efficacy against the third larval stage at all tested concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Also, they reported that the percentages of deformed pupae and malformed adults were the highest with pyridalyl application (10.8 and 22.0%) comparing to spinosad application (2.2 and 3.3%), respectively. Osman and Mahmoud (2009) found that spinosad at its recommended rate against 3 rd instar larvae of S. littoralis susceptible strain resulted in 33.3% pupation, 13.3% adult emergence and 6.6% malformed adults. CONCLUSION…”
Section: Latent Effects Of the Tested Insecticides On S Littoralismentioning
confidence: 97%